2016
DOI: 10.1016/j.bj.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency ablation of tumor feeding artery before target tumor ablation may reduce local tumor progression in hepatocellular carcinoma

Abstract: BackgroundLocal tumor progression (LTP) in early-stage hepatocellular carcinoma (HCC) after radiofrequency ablation (RFA) remains high. Tumor feeding artery ablation (FAA) before target tumor ablation was reported to reduce LTP in patients with HCC >3 cm. The aim of our study is to investigate whether FAA before target tumor ablation may reduce LTP in HCC <3 cm.MethodsWe retrospectively analysis the outcome of patients with HCC <3 cm undergoing FAA before target tumor ablation (N = 17) compared to direct RFA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 23 publications
(40 reference statements)
1
14
0
Order By: Relevance
“…In this retrospective analysis of 52 patients with small (<3 cm) HCC, Cheng et al. [16] find that thermal ablation of the feeding artery before RFA against the target tumor significantly reduces local tumor progression.…”
Section: Also In This Issuementioning
confidence: 99%
“…In this retrospective analysis of 52 patients with small (<3 cm) HCC, Cheng et al. [16] find that thermal ablation of the feeding artery before RFA against the target tumor significantly reduces local tumor progression.…”
Section: Also In This Issuementioning
confidence: 99%
“…For example, real-time 3 D-CEUS could provide richer and more intuitive information on feeding arteries [16], which facilitated the procedure of FAA. Some researchers inserted the electrodes to the area where the arteries surrounded or entered the tumor [11][12][13]15], and another even punctured the nearby blood vessel directly [14]. In fact, this kind of manipulation has a risk of vessel damage, causing occlusion, thrombus, bleeding, or fatal liver infarction [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Another way to reduce or block tumor perfusion is the direct ablation of the target blood vessel before conventional RFA, as a one-step strategy. Previous studies have demonstrated that ultrasound-guided feeding artery ablation (FAA) before conventional RFA, either through percutaneous or laparoscopic access, could safely decrease LTP after HCC ablation [11][12][13][14][15]. However, most of the researchers only use color Doppler imaging to evaluate feeding artery structure and tumor perfusion change [11][12][13][14], which are obviously not precise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations